Pathophysiology, management and therapeutic challenges of coagulopathy in COVID-19 patients - Aliyu, Abdullahi; Kwaifa, Ibrahim Kalle; Danjuma, Bashir Abdulhamid; Bagudo, Aliyu Ibrahim; Zama, Isah Isaac; Rawahi, Qais Al; Elnagger, Mahmoud; Abubakar, Adamu Abdul (Edelweiss Applied Science and Technology, 2025)
The pathophysiology of COVID-19-associated coagulopathy is characterized by a complex of interactions within viral factors, abnormal haemostasis, dysfunction of endothelial cells, and inflammatory reactions, necessitating the research to elucidate underlying mechanisms and identify novel therapeutic targets. Severe COVID-19 conditions are frequently coupled with an increased immunological response, dubbed a cytokine storm, which facilitates the release of pro-inflammatory cytokines (e.g., interleukin-6, tumour necrosis factor-alpha). The cytokine storm contributes to widespread inflammation and endothelial activation, disrupting the balance between pro-coagulant and anticoagulant factors. Additionally, it is capable of being transmitted by contacting surfaces that are contaminated and then rubbing the face. Biomarkers such as D-dimer levels serve as valuable tools in risk assessment and monitoring, yet their interpretation requires careful consideration within the clinical context. Although some COVID-19 patients may not exhibit any symptoms, they can still spread the virus to others, and there is proof that the virus can spread via the air in some environments, especially confined areas with inadequate ventilation. Vaccines have been developed and deployed globally to prevent COVID-19 infection and reduce severe illness, hospitalizations, and deaths. Governments and health authorities worldwide have implemented policies including lockdowns, social isolation, mask-wearing, investigation, contact tracking, and vaccination campaigns to control transmission and reduce the impact of the virus. Data were sorted from PubMed, Google Scholar, Springer, Nature, Tailor and Francis, MDPI, BMC and some other related data. This review provides appreciable information on the pathophysiology, management and therapeutic challenges of coagulopathy in Covid-19 patients.